Blastulation rate using fresh versus devitrified oocytes using homologous and heterologous sperm in an assisted reproduction clinic in a middle-income country - Hidalgo-Carrera, Jaime Antonio; Lezama-Ruvalcaba, Jorge L.; Salazar-Lopez Ortiz, Carlos G.; Salazar-Trujillo, Jose Carlos; Rodriguez-Calderon, Ricardo; Tellez-Velasco, Sergio; Mancilla-Hernandez, Fernando (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2024)
Background: Assisted reproduction has revolutionized the field of reproductive medicine, giving hope to many couples who face difficulties conceiving naturally. In this case, fresh oocytes and devitrified oocytes play a fundamental role in fertility treatments. Methods: Descriptive, retrospective and observational study in which the records of the HISPAREP reproduction clinic of the Spanish hospital were analyzed in the period from 2020 to 2022. Results: A total of 136 blastocysts that reached day 5 were studied compared to 8 embryos that were blocked before reaching blastulation. Of this, 76 oocytes were fresh, of which 97.4% reached day 5 (74) and the remaining two were blocked. Of the vitrified ones, a total of 68 were devitrified and of these 91.2% reached D5. Of the correctly fertilized oocytes, 96.5% (136) reached blastocysts compared to 5 that were blocked and 3 that were blocked from those that were not fertilized. Regarding the fertilization rate of fresh oocytes, a total of 76 was obtained, which is equivalent to 100%, and of the devitrified oocytes, 65 were fertilized (95.6%) and 3 were not fertilized (4.4%). With a variation of 6.2% in the blastocyst rate, between fresh and devitrified oocytes. Conclusions: There is no significant difference in the reproductive results of fresh and vitrified oocytes. It is necessary to try to carry out more studies with a larger sample size to obtain more conclusive results. The reproductive outcomes of fresh oocytes and oocytes devitrified using fresh sperm and frozen sperm are similar. With this, fresh oocytes have a slightly higher probability of implantation.